Concert repertoire as a precondition for performance competence formation of music educator - Anatolievna, Meleshkina Elena; Vera Alexandrovna, Ovsyannikova; Vera Petrovna, Trifanova; Alexandr Petrovich, Tsilinko; Smirnova, Maria Arkadievna (Opción, 2019)
This article examines teaching, pedagogical and concert repertoire as a precondition for performance competence formation of music educator, as well as defines the repertoire aims, tasks, and selection criteria via the method of comparing the role of suggestion and explanation in the process of music’s education. As a result, repertoire plays an important role in acquiring technical skills and competence by singers or instrumentalists and in forming the performing culture of the future music educator. In conclusion, the repertoire is the most important comprehensive component of musical and performing training.